Androgen-induced exosomal miR-379-5p release determines granulosa cell fate: cellular mechanism involved in polycystic ovaries - Reza Salehi; Brandon A. Wyse; Meshach Asare-Werehene; Fereshteh Esfandiarinezhad; Atefeh Abedini; Bo Pan; Yoko Urata; Alex Gutsol; Jose L. Vinas; Sahar Jahangiri; Kai Xue; Yunping Xue; et al. (BMC, 2023)
Abstract Polycystic ovarian syndrome (PCOS) is a complex multi-factorial syndrome associated with androgen excess and anovulatory infertility. In the current study, we investigated the role of dihydrotestosterone-induced exosomal miR-379-5p release in determining the destiny of the developing follicles. Our hypothesis was that androgen regulates granulosa cell miR-379-5p content by facilitating its exosomal release in a follicular-stage dependent manner, a process which determines granulosa cell fate. Compared to human non-PCOS subjects, individuals with PCOS exhibit higher follicular fluid free testosterone levels, lower exosomal miR-379-5p content and granulosa cell proliferation. Androgenized rats exhibited lower granulosa cell miR-379-5p but higher phosphoinositide-dependent kinase-1 (PDK1; a miR-379-5p target) content and proliferation. Androgen reduced granulosa cell miR-379-5p content by increasing its exosomal release in preantral follicles, but not in antral follicles in vitro. Studies with an exosomal release inhibitor confirmed that androgen-induced exosomal miR-379-5p release decreased granulosa cell miR-379-5p content and proliferation. Ovarian overexpression of miR-379-5p suppressed granulosa cell proliferation, and basal and androgen-induced preantral follicle growth in vivo. These findings suggest that increased exosomal miR-379-5p release in granulosa cells is a proliferative response to androgenic stimulation specific for the preantral stage of follicle development and that dysregulation of this response at the antral stage is associated with follicular growth arrest, as observed in human PCOS.